The politics of artificial dunes: Sustainable coastal protection measures and contested socio-natural objects - Gesing, Friederike (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Worldwide, an emerging trend can be observed towards coastal management that works “with nature” – and not against it. A growing “community of practice” (Wenger 1998) is getting involved into projects of so-called “soft” coastal protection. The paper localises the emergence of this “sociotechnical imaginary” (Jasanoff 2015) at the Aotearoa New Zealand coast. It provides an ethnographic analysis of soft coastal protection as a socio-material practice, focusing on coastal dune reshaping. This technique promises a sustainable approach to coastal management that overcomes dualist meanings of coastal protection, understood either as erosion control and property protection, or as nature conservation (Cooper and McKenna 2008). Two examples from the North Island of Aotearoa New Zealand are analysed: a successful project in Whangapoua Beach (Coromandel Peninsula), where dune reshaping has been used by local houseowners as a temporary alternative to a seawall, and the “dune enhancement” part of a contested, Council-commissioned seawall construction project in Waihi Beach (Western Bay of Plenty), which has been perceived as utter failure. The cases show that when soft coastal protection projects are put into practice, the recognition and inclusion of local stakeholders can have manifest material consequences. The paper therefore argues that sustainable coastal protection is not only a technical question, but has a sociomaterial dimension. In order for artificial dunes to “work” as socio-natural objects, local understandings of the rights and responsibilities to care for the coast need to be considered.